Role of Renin-Angiotensin System and Oxidative Stress on Vascular Inflammation in Insulin Resistence Model - N. F. Renna; C. Lembo; E. Diez; R. M. Miatello (International Journal of Hypertension)
(1) This study aims to demonstrate the causal involvement of renin angiotensin system (RAS) and oxidative stress (OS) on vascular inflammation in an experimental model of metabolic syndrome (MS) achieved by fructose administration to spontaneously hypertensive rats (FFHR) during 12 weeks. (2) Chronic treatment with candesartan (C) (10 mg/kg per day for the last 6 weeks) or 4OH-Tempol (T) (10−3 mmol/L in drinking water for the last 6 weeks) reversed the increment in metabolic variables and systolic blood pressure. In addition, chronic C treatment reverted cardiovascular remodeling but not T. (3) Furthermore, chronic treatment with C was able to completely reverse the expression of NF-κB and VCAM-1, but T only reduced the expression. C reduced the expression of proatherogenic cytokines as CINC2, CINC3, VEGF, Leptin, TNF-alpha, and MCP-1 and also significantly reduced MIP-3, beta-NGF, and INF-gamma in vascular tissue in this experimental model. T was not able to substantially modify the expression of these cytokines. (4) The data suggest the involvement of RAS in the expression of inflammatory proteins at different vascular levels, allowing the creation of a microenvironment suitable for the creation, perpetuation, growth, and destabilization of vascular injury.